1987
DOI: 10.1111/j.1744-7348.1987.tb01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of mushroom pests to the insect‐parasitic nematodes Steinernema feltiae and Heterorhabditis heliothidis

Abstract: S U M M A R YThe potential of two species of insect-parasitic rhabditid nematodes (Steinernema feltiae. Heterorhabditis heliothidis) for biological control of mushroom flies was studied in pot trials. Three Diptera that commonly infest mushroom crops were used; the larvae of Megaselia halterata (Phoridae), Heteropeza pygmaea (Cecidomyiidae) and Lycoriella auripila (Sciaridae) were all susceptible to parasitism by both nematode species. Fewer adult phorids and sciarids emerged when compost was nematode-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…Mean percentage emergence of adult shore flies exposed to the 50 IJs/cm 2 of entomopathogenic nematodes, and efficacy of the five nematode species for the control of shore flies in algae bioassay Our results showed that in the majority of treatments an increase in the nematode dosage does not necessarily cause an increase of the shore fly larvae mortality. Similar results were obtained when comparing different nematode concentrations against other dipteran larvae the size of which corresponded to that of shore fly larvae, such as Lycoriella mali (Diptera: Sciaridae) (Grewal and Richardson, 1993;Richardson, 1987;Scheepmaker et al, 1998;Tomalak, 1994). Peters and Ehlers (1994) showed within a species of Tipula that the smaller larvae do not respond as well to increasing nematode doses than the bigger larvae.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Mean percentage emergence of adult shore flies exposed to the 50 IJs/cm 2 of entomopathogenic nematodes, and efficacy of the five nematode species for the control of shore flies in algae bioassay Our results showed that in the majority of treatments an increase in the nematode dosage does not necessarily cause an increase of the shore fly larvae mortality. Similar results were obtained when comparing different nematode concentrations against other dipteran larvae the size of which corresponded to that of shore fly larvae, such as Lycoriella mali (Diptera: Sciaridae) (Grewal and Richardson, 1993;Richardson, 1987;Scheepmaker et al, 1998;Tomalak, 1994). Peters and Ehlers (1994) showed within a species of Tipula that the smaller larvae do not respond as well to increasing nematode doses than the bigger larvae.…”
Section: Discussionsupporting
confidence: 77%
“…The use of predatory mites Hypoaspis miles and H. aculeifer (Acarina: Laelapidae) against Scatella tenuicosta has been tested with success by Va¨nni-nen and Koskula (2004). Entomopathogenic nematodes have also been used against different diptera that live in similar habitat than shore flies, such as phorids (Richardson, 1987;Scheepmaker et al, 1998;Long et al, 2000) and different fungus gnat species such as Bradysia paupera (Gouge and Hague, 1995), Bradysia coprophila (Lindquist and Piatkowski, 1993;Harris et al, 1995;Jagdale et al, 2004), Lycoriella auripila (Richardson and Grewal, 1991;Grewal and Richardson, 1993) and Lycoriella solani (Tomalak, 1994). Previous experiments showed that entomopathogenic nematodes [Steinernema carpocapsae (Weiser) and Steinernema feltiae (Filipjev)] could provide a good control of shore fly larvae (Gouge, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Sciarid larvae cause severe damage to mycelia and developing primordia pinheads as well as to stems and caps of mushrooms (Hussey et al, 1969;McDonald, 1972;Binns, 1975;Clift, 1979b;Garcha et al, 1987 ). The adult sciarids irritate mushroom pickers and act as vectors of mushroom diseases (Richardson, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…They are successfully used to control pest insects in horticultural crops, e.g. the black vine weevil Otiorhynchus sulcatus (Simons, 1981;Kakouli-Duarte et al, 1997) and the mushroom fly Lycoriella auripila (Richardson, 1987;Nickle and Cantelo, 1991). However, experiments with epn aiming to control D. radicum in the field yielded inconsistent results.…”
Section: Introductionmentioning
confidence: 99%